Hepatitis B virus infection in US correctional facilities: a review of diagnosis, management, and public health implications. - Gupta, Shaili; Altice, Frederick L (Journal of urban health : bulletin of the New York Academy of Medicine, 2009)
Among the blood-borne chronic viral infections, hepatitis B virus (HBV) infection is one that is not only treatable but also preventable by provision of vaccination. Despite the availability of HBV vaccine for the last 15 years, more than 1.25 million individuals in the USA have chronic HBV infection, and about 5,000 die each year from HBV-related complications. From a societal perspective, access to treatment of chronic viral infections, like HIV and viral hepatitis, is highly cost-effective and has lasting benefits by reducing risk behaviors, morbidity, mortality, as well as disease transmission in the community. Individuals in correctional facilities are specially predisposed to such chronic viral infections because of their high-risk behaviors. The explosion of incarceration in the USA over the last few decades and the disproportionate burden of morbidity and mortality from chronic infections among the incarcerated have put incredible strains on an overcrowded system that was not originally designed to provide comprehensive medical care for chronic illnesses. Recently, there has been a call to address medical care for individuals with chronic medical conditions in correctional settings, including those with infectious diseases. The economic and public health burden of chronic hepatitis B and its sequelae, including cirrhosis and hepatocellular carcinoma, is felt most prominently in managed care settings with limited budgets, like correctional facilities. Prevalence of HBV infection among the incarcerated in the USA is fivefold that of the general population. We present a review of diagnosis, prevention, and the recently streamlined treatment guidelines for management of HBV infection in correctional settings, and discuss the implications and public health impact of these measures.
Keywords: Adult; Clinical Protocols; Continuity of Patient Care; Drug Resistance, Viral; Female; Hepatitis B; Hepatitis B virus; Humans; Male; Middle Aged; Prisoners; Public Health; United States